MiRNAs differentially expressed in vegetative and reproductive organs of Marchantia polymorpha - insights into their expression pattern, gene structures and function - Aggarwal, Bharti; Karlowski, Wojciech Maciej; Nuc, Przemyslaw; Jarmolowski, Artur; Szweykowska-Kulinska, Zofia; Pietrykowska, Halina (RNA biology, 2024)
MicroRNAs regulate gene expression affecting a variety of plant developmental processes. The evolutionary position of Marchantia polymorpha makes it a significant model to understand miRNA-mediated gene regulatory pathways in plants. Previous studies focused on conserved miRNA-target mRNA modules showed their critical role in Marchantia development. Here, we demonstrate that the differential expression of conserved miRNAs among land plants and their targets in selected organs of Marchantia additionally underlines their role in regulating fundamental developmental processes. The main aim of this study was to characterize selected liverwort-specific miRNAs, as there is a limited knowledge on their biogenesis, accumulation, targets, and function in Marchantia. We demonstrate their differential accumulation in vegetative and generative organs. We reveal that all liverwort-specific miRNAs examined are encoded by independent transcriptional units. MpmiR11737a, MpmiR11887 and MpmiR11796, annotated as being encoded within protein-encoding genes, have their own independent transcription start sites. The analysis of selected liverwort-specific miRNAs and their pri-miRNAs often reveal correlation in their levels, suggesting transcriptional regulation. However, MpmiR11796 shows a reverse correlation to its pri-miRNA level, suggesting post-transcriptional regulation. Moreover, we identify novel targets for selected liverwort-specific miRNAs and demonstrate an inverse correlation between their expression and miRNA accumulation. In the case of one miRNA precursor, we provide evidence that it encodes two functional miRNAs with two independent targets. Overall, our research sheds light on liverwort-specific miRNA gene structure, provides new data on their biogenesis and expression regulation. Furthermore, identifying their targets, we hypothesize the potential role of these miRNAs in early land plant development and functioning.